Karl Holl, Lutherrenaissance und neue Sittlichkeit - Pawlas, Andreas (Kerygma und Dogma, 2018)
After World War I, Karl Holl used the Lutheran doctrine of justification to orient a wandering German people on matters of economic ethics. In the process he dealt critically with Calvin and with Troeltsch's social devaluation of Lutheranism. However, there are hardly any significant differences between the Reformers' positions on economic ethics. And with regard to the issues of greed, interest, and profit that led to the recent financial crisis, it can be stated that Calvin did not recommend a purely economic or even greedy attitude but rather resisted this. Nonetheless, Calvin may well have been stronger than Luther in acknowledging private initiative, self-interest, and profit-seeking as drivers of economic action, and more open to the rational monetary economy that developed in the sixteenth century. However, this does not call into question the fruitfulness of Luther's approach to the economy in general and to the issues of interest and usury in particular on the basis of the doctrine of justification. The direct responsibility to God in interest-taking and economic activity in general, as well as the inclusion of charity in economic life, as discussed by Luther, remain indispensable for Christianity.